How does spending time outdoors protect against myopia? A review. Issue 5 (13th November 2019) - Lingham, Gareth; Mackey, David A; Lucas, Robyn; Yazar, Seyhan
Abstract : Myopia is an increasingly common condition that is associated with significant costs to individuals and society. Moreover, myopia is associated with increased risk of glaucoma, retinal detachment and myopic maculopathy, which in turn can lead to blindness. It is now well established that spending more time outdoors during childhood lowers the risk of developing myopia and may delay progression of myopia. There has been great interest in further exploring this relationship and exploiting it as a public health intervention aimed at preventing myopia in children. However, spending more time outdoors can have detrimental effects, such as increased risk of melanoma, cataract and pterygium. Understanding how spending more time outdoors prevents myopia could advance development of more targeted interventions for myopia. We reviewed the evidence for and against eight facets of spending time outdoors that may protect against myopia: brighter light, reduced peripheral defocus, higher vitamin D levels, differing chromatic spectrum of light, higher physical activity, entrained circadian rhythms, less near work and greater high spatial frequency (SF) energies. There is solid evidence that exposure to brighter light can reduce risk of myopia. Peripheral defocus is able to regulate eye growth but whether spending time outdoors substantially changes peripheral defocus patterns and how this could affect myopia risk is unclear. Spectrum of light, circadian rhythms and SF characteristics are plausible factors, but there is a lack of solid evidence from human studies. Vitamin D, physical activity and near work appear unlikely to mediate the relationship between time spent outdoors and myopia.